2022
DOI: 10.1021/acs.joc.2c01385
|View full text |Cite
|
Sign up to set email alerts
|

3-Alkyl-2-pyridyl Directing Group-Enabled C2 Selective C–H Silylation of Indoles and Pyrroles via an Iridium Catalyst

Abstract: An iridium-catalyzed, directing group-enabled site selective intra- and intermolecular silylation of indoles and pyrroles with hydrosilanes has been developed under ligand-free conditions. Fine-tuning of the removable 3-alkyl-2-pyridyl directing group was found to be crucial for achieving high yields for C2-silylated indole and pyrrole products. Moreover, the scalability was demonstrated, and further transformations of the silylation products were achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Template for SYNTHESIS Thieme In 2022, the Yang group reported a ligand free directed C2selective intra-and intermolecular C−H silylation strategy for indoles and pyrroles (25) via iridium catalysis (Scheme 8). 19 In this study, the directing group ( This article is protected by copyright. All rights reserved.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Template for SYNTHESIS Thieme In 2022, the Yang group reported a ligand free directed C2selective intra-and intermolecular C−H silylation strategy for indoles and pyrroles (25) via iridium catalysis (Scheme 8). 19 In this study, the directing group ( This article is protected by copyright. All rights reserved.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In 2022, the Yang group reported a ligand-free directed C2-selective intra-and intermolecular C-H silylation strategy for indoles and pyrroles 25 via iridium catalysis (Scheme 8). 19 In this study, the directing group (3-alkyl-2-pyridyl) plays a crucial role in controlling the regioselectivity. From several control experiments, reversibility of the C-H cleavage steps was observed, and it was therefore concluded that Si-H bond cleavage instead of C-H bond cleavage at the C2 position of indole might be involved in the rate-limiting step in this reaction.…”
Section: Special Topic Synthesismentioning
confidence: 99%
“…Taken together, these results support the reversibility of the ortho C-H bond cleavage step and suggest that the Si-H bond breaking, and not the C-H bond, is involved in the rate-determining step. 20,21 Finally, the catalytic silylation of substrate 3a conducted in the presence of access butylated hydroxytoluene (BHT), TEMPO [2,2,6,6-tetramethylpiperidine-1-oxyl], or mercury metal proceeded without noticeable decrease of activities (Fig. S11 and S12, ESI †), implying This journal is © The Royal Society of Chemistry 2023 that both the involvement of free radical processes or heterogeneous catalysis are unlikely to be operative.…”
mentioning
confidence: 99%